Integrated nanoscale electronics and optoelectronics: Exploring nanoscale science and technology through semiconductor nanowires - Huang, Yu; Lieber, C. M. (Pure and applied chemistry, 2004)
Semiconductor nanowires (NWs)represent an ideal system for investigating low-dimensional physics and are expected to play an important role as both interconnects and functional device elements in nanoscale electronic and optoelectronic devices. Here we review a series of key advances defining a new paradigm of bottom-up assembling integrated nanosystems using semiconductor NW building blocks. We first introduce a general approach for the synthesis of a broad range of semiconductor NWs with precisely controlled chemical composition, physical dimension, and electronic, optical properties using a metal cluster-catalyzed vapor-liquid-solid growth mechanism. Subsequently, we describe rational strategies for the hierarchical assembly of NW building blocks into functional devices and complex architectures based on electric field or micro-fluidic flow. Next, we discuss a variety of new nanoscale electronic device concepts including crossed NW p-n diode and crossed NW field effect transistors (FETs). Reproducible assembly of these scalable crossed NW device elements enables a catalog of integrated structures, including logic gates and computational circuits. Lastly, we describe a wide range of photonic and optoelectronic devices, including nanoscale light-emitting diodes (nanoLEDs), multicolor LED arrays, integrated nanoLED-nanoFET arrays, single nanowire waveguide, and single nanowire nanolaser. The potential application of these nanoscale light sources for chemical and biological analyses is discussed.